2022
DOI: 10.1111/bph.15745
|View full text |Cite
|
Sign up to set email alerts
|

Proteinase‐activated receptor‐2 antagonist C391 inhibits Alternaria‐induced airway epithelial signalling and asthma indicators in acute exposure mouse models

Abstract: Background and Purpose Despite the availability of a variety of treatment options, many asthma patients have poorly controlled disease with frequent exacerbations. Proteinase‐activated receptor‐2 (PAR2) has been identified in preclinical animal models as important to asthma initiation and progression following allergen exposure. Proteinase activation of PAR2 raises intracellular Ca2+, inducing MAPK and β‐arrestin signalling in the airway, leading to inflammatory and protective effects. We have developed C391, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 67 publications
0
23
0
Order By: Relevance
“…It should be noted, however, that inhibiting PAR2 in HNE and HBE cells did not completely reduce intracellular calcium or ATP release, cytokine or mucin secretion, or inflammation, suggesting additional PAR2‐independent mechanism(s) for allergic responses 45,74,81,91 . This is supported by recent studies showing non‐protease activation of the MAPK pathway, 98 and attenuated not abrogated responses in PAR‐deficient mice 13 …”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…It should be noted, however, that inhibiting PAR2 in HNE and HBE cells did not completely reduce intracellular calcium or ATP release, cytokine or mucin secretion, or inflammation, suggesting additional PAR2‐independent mechanism(s) for allergic responses 45,74,81,91 . This is supported by recent studies showing non‐protease activation of the MAPK pathway, 98 and attenuated not abrogated responses in PAR‐deficient mice 13 …”
Section: Discussionmentioning
confidence: 81%
“…Fungal proteases and PAR2 were identified as key contributors to fungal allergy in 19 (31%) and 13 (21%) studies, the 1st and joint 3rd most studied molecules respectively. Fungal proteases have been shown to promote mucin production, goblet cell hyperplasia and AHR 98 . Heat inactivation and protease inhibition confirmed that fungal proteases activated the PAR2 receptor in both bronchial and small airway cell lines as well as primary HNE cells 37,43,81 .…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…111,112 Alternaria alkaline serine protease activates PAR2 directly and induces allergic airway inflammation in mice. 106 Additionally, various fungal allergen extracts, including Alternaria 113,114 and Aspergillus 115 extracts, have been shown to activate AEC, eosinophils, and induce cytokines through PAR2 but the exact proteases mediating these effects have not been identified. 116 Fungal Pen c 13 can cleave PAR1 and PAR2 at their activation sites and desensitize AECs to increased intracellular calcium induced by PAR1 and PAR2 agonists.…”
Section: Prote a S E-ac Tivated Recep Tor (Par ) Ac Tivati On By Prot...mentioning
confidence: 99%
“…Male mice were used due to their enhanced response to allergens that allowed for statistical analysis with a reduced amount of animals. At 8 weeks, mice were randomly divided into four treatment groups of six mice each and subjected to allergen sensitization and challenge using A. alternata filtrate as described (Rivas et al, 2021). Mice were first anaesthetised by placing them in a chamber supplied with vaporized isoflurane and oxygen.…”
Section: In Vivo Experimentsmentioning
confidence: 99%